Songs of the Lisu Hills : practicing Christianity in southwest China - Arrington, Aminta (World Christianity (University Park, Pa.), 2020)
"Explores the history and practice of Lisu Christianity in southwest China, describing how the Lisu maintained their Christian faith through China's tumultuous twentieth century and into the present"--